Risk Factors for Prolonged Mechanical Ventilation Post Cardiac Surgery in Al Thawra Hospital, Sana'a, Yemen - Abdulrahman Al Aizary,; Faiz Daud, (Universiti Kebangsaan Malaysia, 2016)
Introduction: Prolonged mechanical ventilation among cardiac surgery patient has been found to be correlated with negative clinical outcome and increased healthcare resources utilization. Prolonged mechanical ventilation(PMV) was defined as the accumulative duration of 24 hours or more of postoperative endotracheal intubation starting from transfer of the patient to cardiac ICU. This study is aimed to identify the risk factors preoperative, intra operative and postoperative for prolonged ventilation among cardiac patients in AL-Thawra Modern General Hospital(TMGH). Methods: Observational study design was conducted during a two-month period (from 1 August 2014 to 30 September 2014). It was among 70 patients who were admitted to cardiac surgery intensive care unit in Al-Thawra Modern General Hospital and selected by convenient sampling. The soci-demographic characteristic and clinical patient data were collected using short questionnaire developed by researcher. All patients had the same anesthetic and postoperative management. Statistical analysis was performed with SPSS version 20 and using bivariate analysis and multivariate logistic regression. The p-value of < 0.05 was found to be statistically significant. Results: Incidence of prolonged mechanical ventilator post cardiac surgery was 37.1% (26/70) through bivariate analysis, multivariate logistic regression. Low Ejection fraction of Left Ventricle was inversely related to mechanical ventilation time (AOR= 0.872) with 95% confidence interval [0.790 - 0.963], hemodynamic instability were associated with prolonged mechanical ventilation time (AOR=16.35) with 95% confidence interval [2.558 - 104.556]. Conclusion: Low ejection fraction of Left Ventricle and Hemodynamic Instability post operation were identified risk factors for prolonged mechanical ventilation post cardiac surgery.